The associations between oxidative balance score and serum Klotho level in the U.S. population aged 40–79 years - Kang Wang; Zhongbiao Jiang; Qin Zhou; Hanfen Tang (Scientific Reports)
Abstract The relationship between the oxidative balance score (OBS) and the serum Klotho level has yet to be defined. We sought to investigate the potential relationship between OBS and the serum Klotho level in the U.S. population aged 40–79 years. This study included 8,145 participants from the National Health and Nutrition Examination Surveys (NHANES) database spanning from 2007 to 2016. The OBS consisted of the dietary OBS and the lifestyle OBS, based on 16 dietary components and 4 lifestyle components. Weighted multiple linear regressions were performed to explore the association between OBS and serum Klotho level. Furthermore, nonlinear relationships were analyzed through the application of restricted cubic splines (RCS). In the multivariate linear regression model with adjustment for such as demographics, economic income and dietary intake, a higher OBS was associated with a higher serum Klotho, with the beta estimate and 95%CI of 2.85 (1.03–4.68, p < 0.01). Compared with the lowest tertile group, the highest group was associated with a higher Klotho level (30.35, 3.43–57.28, p < 0.05). Furthermore, higher dietary OBS and lifestyle OBS were similarly associated with higher Klotho level (beta (95%CI): 1.27 (0.79–3.32); 14.23 (9.53–18.92), respectively). The RCS exhibited a linear dose-response association between OBS, dietary OBS and lifestyle OBS with serum Klotho concentration (P non−linearity>0.05). The association between OBS and serum Klotho level was consistent across age, sex, education, marital status, energy intake and poverty income ratio (PIR) (P interaction>0.05). The study reported significant association between OBS and klotho, indicating that adherence to antioxidant behaviors may be linked to slower aging and better health.